KERJASAMA INDONESIA DAN NORWEGIA DALAM MENGURANGI EMISI GAS KARBON (STUDI KASUS : PENGELOLAAN KAWASAN HUTAN DI KALIMANTAN BARAT TAHUN 2008-2012) - Harry Sidiq Habbibillah; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how the Partnership Between Indonesia – Norway through Reducing Carbon Emissions. The objects of this study is the West Kalimantan forest, REDD scheme and the cooperation between Indonesia – Norway. Researchers are trying to understand and analyze the forest damage in Indonesia and the role of REDD in an effort to minimize the damage.This study used qualitative research type. The research method used is descriptive analysis techniques. Most of the data collected through the literature, searching websites, and interviews. Those data were analyzed by theory approach based on International Relations, Foreign Policy, International Cooperation, International Agreement, and Environmental.The results of this study indicate that the cooperation between Indonesia – Norway through the REDD scheme is poured into the form of a Letter of Intent (LoI) agreed on three phases in order to save West Kalimantan’s forest despite undergoing a new stage in the first phase, this cooperation has resulted although not significantly.Keywords : Environmental, REDD, Indonesia, Norway, West Kalimantan’s Forest